SPECTROPHOTOMETRIC EVALUATION OF NIMESULIDE IMPURITY D: 4-NITRO-2- PHENOXYANILINE USING 8-HYDROXYQUINOLINE AS OXIDATIVE COUPLING REAGENT - S, Anil Kumar; Bl, Bhaskar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Spectrophotometric investigation of 4-nitro-2-phenoxyaniline (4N2PA), a probable intermediate during the synthesis of anti-inflammatory drug nimesulide, both in pure form and in the presence of nimesulide has been attempted. Methods: 4N2PA on diazotization followed by coupling with 8-hydroxyquinoline produces a crimson-colored complex which changes to deep violet on diluting with ethanol. Results: The complex showed maximum absorbance at 560 nm when evaluated spectrophotometrically with a detection limit of 0.005 Î¼g/ml and quantification range of 0.05-3.0 Î¼g/ml. The method has been statistically evaluated with respect to the International Council for Harmonisation guidelines and found to be accurate and precise. Conclusion: Pure tablet formulations of nimesulide do not respond to the method; however, the presence of minute amounts of 4N2PA in the drug as added impurity could be spectrophotometrically analyzed. Hence, the authors suggest that the reported technique could be a marker test for detecting the presence of 4N2PA in nimesulide formulations.